Komunikasi Transendental dalam Ritual Membuat Periuk Tanah - Oktaviana Lestry Kolo; Aloysius Liliweri; Ferly Tanggu Hana (Universitas Nusa Cendana, 2019)
This research aims to know transcendental communication in making soil stewpot ritual in Wolokoli Village of Bola Subdistrict of Sikka Regency. The object of this research is making soil stewpot rituals done by People in Wolokoli village. This is a phenomenological study with data collected technique through Observation, In-Depth Interview and Documentation. The result of this research showed that transcendental communication done by people in Wolokoli village of Bola Subdistrict of Sikka Regency. Transcendental communication of people in this village with God or ancestors’ soul or the other invisible strength believed by them happens in the ritual or in the production process of a traditional handicraft that known as unu tana Wolokoli. Especially for making the soil stewpot, a ritual held in the stone plate in one of the craftsman's houses corner and held by the craftsmen his own (woman only) helped by one of her family. This ritual held before makes the soil stewpot. Ritual held in the house corner aims to give offerings for ancestors’ souls in the hope of the ancestors’ souls always guide them in making soil stewpot process.